Pengaruh E-money terhadap Jumlah Uang Beredar dan Velocity of money dengan Inflasi sebagai Variabel Mediasi - Andika Pratama Sitepu (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Based on the results of partial testing of the effect of E-Money on Inflation, the t.count value = 1.851 is greater than the t.table value = 1.667 with sig, 0.000<0.05 from these results it can be concluded that Ha is accepted, this indicates that E-Money has a significant effect on Inflation. The partial test results of the influence of E-Money on the Amount of Money in Circulation obtained a t-value of 2.204 greater than the t-table value of 1.667 with sig. 0.000 <0.05 from these results it can be concluded that Ha is accepted, this shows that E-Money has a significant influence on the Amount of Money in Circulation. Based on the partial test results of the influence of Velocity of money on Velocity of money, the t-value of 2.487 is greater than the t-table value of 1.667 with sig. 0.001 <0.05 from these results it can be concluded that Ha is accepted, this shows that the Amount of Money in Circulation has a significant influence on Velocity of money.